Características estatísticas turbulentas associadas ao fenômeno do vento norte no sul do Brasil: aplicação ao problema da difusão de contaminantes - Arbage, Maria Cristina Andres (2008)
A parameterization for the transport processes in a shear driven planetary boundary layer (PBL) has been established, employing turbulent statistical quantities measured during the north wind phenomenon in southern Brazil. Therefore, observed one-dimensional turbulent energy spectra are compared with a spectral model based on the Kolmogorov arguments. The good agreement obtained from this comparison leads to well defined formulations for the turbulent velocity variances, local decorrelation time scale and eddy diffusivities. Furthermore, for vertical regions in which the wind shear forcing is relevant, the eddy diffusivity derived from the north wind data presents a similar profile as those obtained from the non-extensive statistical mechanics theory. Finally, a validation for the present parameterization has been accomplished, using a Lagrangian stochastic dispersion model. Twind speed, is simulated. The analysis developed in this study shows that the turbulence parameterization constructed from wind data for north wind flow cases is able to describe the diffusion in a high wind speed, shear-dominated PBL.he Prairie Grass data set, which presents high mean